Facile synthesis of polyaniline-silver composites through interfacial polymerization - Abdolahi, Ahmad (2013)
In this paper, the simple synthesis of polyaniline/silver composites through interfacial polymer method was studied. Polyaniline-silver composites were produced at room temperature by using ammonium persulphate as an oxidant agent in presence of silver nitrate (AgNO3). Field Emission Scanning Electron Microscopy (FESEM), X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) techniques were used to characterize the synthesized product. FESEM results showed the core shell shape of composites that the layer of polyaniline covered the silver particles. XRD results showed the high crystalline behaviour of the polyaniline/silver composites due to presence of silver. FTIR results also showed the successfully synthesis of the composite. This paper aims to study on synthesis and characterization of polyaniline-silver composites